Performance of IAC 300 rubber clones in the plateau of São Paulo State, Brazil - Gonçalves, Paulo de Souza; Martins, Antonio Lúcio Mello; Furtado, Edson Luiz; Sambugaro, Rosana; Ottati, Emma Luize; Ortolani, Altino Aldo; Júnior, Gentil Godoy (Pesquisa Agropecuaria Brasileira, 2002)
The present paper shows the results of the selection of IAC 300 serial promising clones of rubber tree (Hevea spp.) for the plateau region of São Paulo State, Brazil. Eighteen clones were selected from a population of 70 clones resulted of controlled pollination, all evaluated in a small scale trial. The trial was laid out in randomized block design with three replications following the 7.0 m x 3.0 m spacing at the Experimental Station of Pindorama. The clones RRIM 600 and GT 1 were used as control. Regarding to yield, eight and ten clones showed superiority to RRIM 600 and GT 1, respectively. All the selected clones showed to be vigorous regarding to the girth by the panel opening. Seven clones showed high resistance, seven with moderate resistance, and two were susceptible to the anthracnose panel canker. A complementary evaluation in large scale trials is to evaluate, besides yielding, other secondary characters, with the purpose of future recommendations in large scale for São Paulo State.